Hubungan thoharoh dan sholat: makna, tata cara, dan pentingnya dalam ibadah - Wardani, Ida Kusuma (Maliki Interdisciplinary Journal, 2026)
Thaharah and salat are two interconnected aspects of worship in Islamic teachings. Thaharah is a way of purifying oneself physically and spiritually, which serves as an absolute prerequisite for performing salat, while salat itself is the core worship that marks a Muslim's faith. This article aims to explain the relationship between thaharah and salat, outline the meaning and correct procedures of thaharah, and reveal the importance of both in worship. This research uses a qualitative method with a literature study approach, referring to the Quran, Hadith, classical fiqh books, and related scientific research. The results show that thaharah is not merely physical cleanliness but also a symbol of spiritual purity to face Allah SWT. The correct procedures for thaharah (wudhu, ghusl, tayammum) are an absolute requirement for salat to be valid. A clear understanding of the relationship between thaharah and salat can improve the quality of worship, as well as have a positive impact on health and spirituality in daily life.